ONE STOP STUDY CENTRE - Hassim, Norfarezan (UNIVERSITI TEKNOLOGI PETRONAS, 2012)
One Stop Study Centre is a website designed to provide all the information on the educational institute and study loans for the Sijil Pelajaran Malaysia (SPM) leaver’s students in Malaysia. The main purpose of this project is to collect all the information of the educational institution and all the respective fields of study that available in the market for the student to choose from. Apart from that, the website will also provide the educational aid that available for the student to choose from when furthering their studies. The website will publish all the fields of studies and the list the educational institution – public and private, in Malaysia. A brief explanation on each of the institution will be included for the student’s reference. Thus, the student will find all the information needed in the One Stop Study Centre Website. This website, which contains all the supportive information on the education field, will help the student to prepare for their education scholarship or the study loan. The results consist of the findings from the literature review section and the storyboard of the website. Recommendation and conclusion conclude the whole chapter of the project and it recommends few recommendations for future implementation of the project.